(3NQjOI GdYLGFH haQjOI GdZQGFHs - (3GHf GdhQOj , YeQ Hf eXaQ Hf YeQ Hf eMeO GHf CHj GdahGQS GdeYQj GdcfOj, Rjf GdOjf CHh MaU,J (B749 (3g` s
(3ChdgG (B:s
(3GdMeO ddg PcQ GdEeGe GdYdGeI GHf GdhQOi ai YLGjH NQjOJg s
(3BNQgG (B:s
(3GfJgi ef GdNQjOI dGHf GdhQO ai HhGSWI s
(3HgG fXGe GdJYbjHIs
(3PcQ GdYfhGf GdCUdi ai c X (B1/ 701s
(3fbhd efg s
(3JHUQI GdYfhGf (B:s
(3GNJjGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdLZQGajG h GdHdOGfs